Nonnutritive, Low Caloric Substitutes for Food Sugars: Clinical Implications for Addressing the Incidence of Dental Caries and Overweight/Obesity. (22nd February 2012) - Roberts, Michael W.; Wright, J. Timothy
Abstract : Caries and obesity are two common conditions affecting children in the United States and other developed countries. Caries in the teeth of susceptible children have often been associated with frequent ingestion of fermentable sugars such as sucrose, fructose, glucose, and maltose. Increased calorie intake associated with sugars and carbohydrates, especially when associated with physical inactivity, has been implicated in childhood obesity. Fortunately, nonnutritive artificial alternatives and non-/low-caloric natural sugars have been developed as alternatives to fermentable sugars and have shown promise in partially addressing these health issues. Diet counseling is an important adjunct to oral health instruction. Although there are only five artificial sweeteners that have been approved as food additives by the Food and Drug Administration (FDA), there are additional five non-/low caloric sweeteners that have FDA GRAS (Generally Recognized as Safe) designation. Given the health impact of sugars and other carbohydrates, dental professionals should be aware of the nonnutritive non-/low caloric sweeteners available on the market and both their benefits and potential risks. Dental health professionals should also be proactive in helping identify patients at risk for obesity and provide counseling and referral when appropriate.